(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The main objective of this study was to determine the extent of adoption of improved potato production technologies by the potato growers. Data were collected from 231 potato growers of three highly concentrated potato growing Upazilas, namely Pirgachha (Rangpur), Munshiganj Sadar (Munshiganj), and Shibganj (Bogra) during October 2010 to February 2011. The potato growers showed marked individual differences in their socio-economic characteristics and majority of them belonged to middle age category having small family size, primary level of education, small farm size, medium innovativeness, and medium contact with extension personnel. The study revealed that highest proportion of the respondents in Munshiganj Sadar belonged to high adoption category in case of BARI recommended potato variety (72.6%), optimum planting time (87.7%), use of balanced fertilizers (45.2%), whereas medium adoption categories were found in quality potato seed (52.1%), proper seed size (47.9%), fertilizer application methods (71.2%), optimum irrigation (89%), earthing up (84.9%), plant protection (74%), and low adoption categories were found in maintaining proper spacing (42.5%). In Pirganj of Rangpur, highest proportion of the respondents belonged to high adoption category in case of BARI recommended potato variety (77%), optimum planting time (83.8%), whereas medium adoption categories were found in the use of quality potato seed (64.9%), balanced fertilizer (43.2%), proper seed size (52.7%), fertilizer application methods (87.8%), optimum irrigation (97.3%), earthing up (86.5%), plant protection (93.2%), and low adoption categories were found in maintaining proper spacing (64.9%). In Shibganj of Bogra, highest proportion of the respondents were found in high adoption category in case of BARI recommended potato variety (75%), optimum planting time (86.9%), whereas medium adoption categories were found in use of quality potato seed (52.4%), balanced fertilizers (47.6%), fertilizer application methods (78.6%), optimum irrigation (95.2%), earthing up (88.1%), plant protection (76.2%), and low adoption categories were found in maintaining proper spacing (59.5%) and proper seed size (57.1%). The study also revealed that highest (53.4%) proportion of the respondents in Munshiganj Sadar belonged to high potato yield (above 29 ton/ha) farmer category while medium potato yield (between 19 to 29 t/ha) category were found in other two areas i.e., Shibganj (58.80%) and Pirgachha (79.50%). Education, farm size, subsistence pressure, annual income, contact with the sources of information, farming experience, attitude, and knowledge on potato production showed significant positive relationship with adoption of improved potato production technologies. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20145 Bangladesh J. Agril. Res. 39(1): 79-92, March 2014